Simulation of five methods for parameter estimation and functionExponential distribution reliability - خضر عبد الجبار; حسون انتصار عبيد; حسين اسيل ناصر (Journal of Economics and Administrative Sciences, 2009)
The estimation process is one of the pillars of the statistical inference process as well as the hypothesis test, and the assessment is based on the collection of information and conclusions about the teacher or the community’s teachers on the basis of the results obtained from the sample drawn from that society. There are several methods for estimating the parameters of a society, such as the usual methods, which depend on the lack of advance information about the parameters to be estimated. There are other methods called the methods, which depend on the assumption that the parameter or parameters to be estimated is a random variable with a function. In order to obtain capabilities with good characteristics, especially if there is more than one method for estimating a parameter, this leads to a study of the differentiation between these capabilities to choose the best ones, based on statistical criteria including bias, variance, average error squares, absolute average error, etc. The researcher analyzes the time of failure or the time it takes until the failure or the impact of life or the failure times of the machines, the probability distribution suitable for these cases is the exponential distribution or the distribution of Kama or distribution Wibel and others. Because of the importance of exponential distribution in the analysis of many survival and reliability times of many devices, we have seen the application of different methods of estimation to estimate the parameters of this distribution, which was addressed by many researchers including but not limited to Sinha & Sloan (1988), Vincenl (1997) and researcher Fernandez (2000), Alfawzan (2000), Nasser (2002), al-Bayati (2002), al-Nasser and al-Bayati (2004) and others. عرض المزيد عرض أقل